2020
DOI: 10.4049/jimmunol.1901440
|View full text |Cite
|
Sign up to set email alerts
|

Secretome-Mediated Interactions with Intestinal Epithelial Cells: A Role for Secretome Components from Lactobacillus rhamnosus R0011 in the Attenuation of Salmonella enterica Serovar Typhimurium Secretome and TNF-α–Induced Proinflammatory Responses

Abstract: This information is current as Proinflammatory Responses Induced − α Secretome and TNF-Serovar Typhimurium Salmonella enterica R0011 in the Attenuation of rhamnosus Lactobacillus Secretome Components from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 98 publications
4
19
1
1
Order By: Relevance
“…Given that inflammation promotes the development of gastric ulcers and cancers, the prevention of inflammation by LAB supernatants is of great clinical significance. Also, these effects are in line with recent studies that showed that the secretome of LAB L25 decreased the inflammatory response of human intestinal cells to Salmonella [41].…”
Section: Lab Secretions Protect Against H Pylori-induced Inflammationsupporting
confidence: 90%
“…Given that inflammation promotes the development of gastric ulcers and cancers, the prevention of inflammation by LAB supernatants is of great clinical significance. Also, these effects are in line with recent studies that showed that the secretome of LAB L25 decreased the inflammatory response of human intestinal cells to Salmonella [41].…”
Section: Lab Secretions Protect Against H Pylori-induced Inflammationsupporting
confidence: 90%
“…Soluble bioactive molecules have also been shown to be secreted by Lactobacillus rhamnosus R0011, down-regulating proinflammatory chemokine production of human HT-29 cells simulated with proinflammatory signaling. Furthermore, LAB–host communication has been shown to mediate the regulation of the expression of crucial immune response signaling genes, such as NF-κB and MAPK, among others [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, Lactobacillus was the predominant genera in the rumen of the R group on day 10, which differs from the B group. Previous research indicated that Lactobacillus plays an important role in maintaining rumen microbiota and improving the digestive power of rumen (37)(38)(39)(40). Additionally, Lactobacillus can also inhibit the proliferation of pathogenic bacteria in the rumen by producing organic acid and antimicrobial peptides (39,40).…”
Section: Discussionmentioning
confidence: 99%